STATE FINANCE AUDIT FOR PEOPLE’S WELFARE (DIALOGUE OF RHETORIC AND REALITY) - Joko Santosa (Universitas Airlangga, 2022)
The purpose of this study to gain an in-depth understanding of the role of audit for the welfare of the people. Qualitative tradition becomes a paradigm of study by using literature study as its methodology. The results of the analysis and discussion, the discourse is more strategically valuable if it is implemented in efforts to handle and minimize corruption. The argument that states that as a form of audit expectation gap, people's welfare is difficult to realize when corruption is still a serious problem that has not been resolved. The practical contribution of this research is to offer two strategic steps that BPK can take to reduce the existing expectation gap, firstly by improving the quality of financial audits, and secondly by focusing on performance audits with a higher priority on improving the quality of internal auditors' performance (APIP). In the theoretical realm, it can open up opportunities for the development of the concept of auditing in the public sector, not only serving scientific needs but also responding to public expectations.